Spatial Mapping Of Coconut Plantation In Minahasa Regency, North Sulawesi Province Using Remote Sensing Data - Wiske Ch. Rotinsulu; Semuel D. Runtunuwu; Hengkie Walangitan; Frangky J. Paat; Badrun Zaini (Sam Ratulangi University, 2022)
Kata kunci: Interpretasi visual, perkebunan, citra satelit